The influence of spin in black hole triplets - Chitan, A.; Mylläri, A.; Valtonen, M. (ELSEVIER, 2025)
Spin can influence the dynamics of the already chaotic black hole triplet system. We follow this problem in two sets of simulations: first, the Agekian-Anosova region (or region D), and second, using Pythagorean triangles. We use ARCcode, an N-body code that performs numerical integration of orbits. This code includes post-Newtonian corrections, which we include up to the 2.5th order. Inset one of our simulations, we fix the masses of the black holes at 106 M circle dot. Then we run the simulations first without any spin added and after by initialising spin on one of the black holes. We find that after including spin into the system, 12.9% of the simulations changed outcomes. Either the systems went from having all black holes merging to having a black hole escaping the system, or vice versa. In the second set of simulations, we expanded into Pythagorean triangles as initial positions of black holes, stemming from Burrau's three-body problem. We varied the masses of the black holes from 100 M circle dot-1012 M circle dot. Black holes in these systems were given spin in normalised units ranging from 0 to similar to 0.95. We find that intermediate mass black holes in the range of 104 M circle dot-105 M circle dot, were influenced the most by spin, particularly in their lifetimes. We also find that simulations, initialised as 2-dimensional, become 3-dimensional.